Muscarinic acetylcholine receptor 3 localized to primary endothelial cilia regulates blood pressure and cognition - Hannah C. Saternos; Kathleen V. Forero; Mahmood A. Meqdad; Raghad Buqaileh; Clare L. Sunderman; Gillian Gallagher; William S. Messer; Ashraf M. Mohieldin; Claudio A. Mucci; Sanjana Kumariya; Islam A. Osman; James P. Burkett; et al. (Scientific Reports)
Abstract We previously demonstrated that the inability of primary endothelial cilia to sense fluid shear stress can lead to nitric oxide (NO) deficiency and cause hypertension (HTN). Decreased biosynthesis of NO contributes to cerebral amyloid angiopathy in Alzheimer’s disease (AD) patients through increased deposition of amyloid beta (Aβ). However, the molecular mechanisms underlying the pathogenesis of HTN and AD are incompletely understood. The objective of this study was to examine the pathophysiological roles of vascular primary cilia and muscarinic acetylcholine receptor 3 (CHRM3) in HTN and AD. We discovered, for the first time, that CHRM3 was localized to primary cilia of endothelial and cerebrovascular cells, and that CHRM3 expression was downregulated in cilialess cells. Moreover, CHRM3 activation enhanced cilia length and sensory function in terms of eNOS activation. To further examine the role of vascular CHRM3 in vivo, we showed that endothelial CHRM3 knockout was associated with increased BP and attenuated acetylcholine-mediated vascular relaxation. In addition, endothelial CHRM3 knockout resulted in altered fear behavior. This demonstrates the physiological significance of endothelial CHRM3 signaling and primary cilia-derived NO production as an important mechanism in the control of BP and cognition.